1965
DOI: 10.1126/science.150.3700.1187
|View full text |Cite
|
Sign up to set email alerts
|

Evoked-Potential Correlates of Stimulus Uncertainty

Abstract: The average evoked-potential waveforms to sound and light stimuli recorded from scalp in awake human subjects show differences as a function of the subject's degree of uncertainty with respect to the sensory modality of the stimulus to be presented. Differences are also found in the evoked potential as a function of whether or not the sensorymodality of the stimulus was anticipated correctly. The major waveform alteration is in the amplitude of a positive-going component which reaches peak amplitude at about 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

41
1,229
3
59

Year Published

1985
1985
2010
2010

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 2,611 publications
(1,360 citation statements)
references
References 5 publications
41
1,229
3
59
Order By: Relevance
“…This initial deflection is followed by the P1 and N1 components as information propagates through the visual system and perceptual analysis is performed (Heinze et al, 1994; Heinze, Mangun, & Hillyard, 1990; Luck, 1995; Vogel & Luck, 2000). 2 Next, we can observe waveforms elicited by the deployment of covert attention to peripheral targets in the visual field (e.g., the N2pc, Eimer, 1996; Luck & Hillyard, 1994a, 1994b) and components associated with categorization of the visual stimulus (e.g., the N2/P3 complex, Kutas, McCarthy, & Donchin, 1977; Pritchard, Shappell, & Brandt, 1991; Sutton, 1979; Sutton et al, 1965). Waveforms indexing working memory encoding and maintenance are the next to come online (i.e., the P3 and contralateral-delay activity, Donchin, 1981; Vogel & Machizawa, 2004), followed by components elicited during the selection and preparation of the motor response (i.e., the lateralized-readiness potential or LRP, Coles, 1989).…”
Section: Why Erps Are Well Suited To Study Perception and Attention?mentioning
confidence: 99%
“…This initial deflection is followed by the P1 and N1 components as information propagates through the visual system and perceptual analysis is performed (Heinze et al, 1994; Heinze, Mangun, & Hillyard, 1990; Luck, 1995; Vogel & Luck, 2000). 2 Next, we can observe waveforms elicited by the deployment of covert attention to peripheral targets in the visual field (e.g., the N2pc, Eimer, 1996; Luck & Hillyard, 1994a, 1994b) and components associated with categorization of the visual stimulus (e.g., the N2/P3 complex, Kutas, McCarthy, & Donchin, 1977; Pritchard, Shappell, & Brandt, 1991; Sutton, 1979; Sutton et al, 1965). Waveforms indexing working memory encoding and maintenance are the next to come online (i.e., the P3 and contralateral-delay activity, Donchin, 1981; Vogel & Machizawa, 2004), followed by components elicited during the selection and preparation of the motor response (i.e., the lateralized-readiness potential or LRP, Coles, 1989).…”
Section: Why Erps Are Well Suited To Study Perception and Attention?mentioning
confidence: 99%
“…The experiment was designed to elicit the P300 ERP (Sutton et al, 1965). The P300 is a parietally distributed EEG potential that occurs around 300 ms after rare occurrences of deviant stimului (called oddballs) embedded in frequent stimuli (called standards).…”
Section: Erp (Event-related Potential) Measurementmentioning
confidence: 99%
“…The impact of salient stimulus processing on brain electrical activity was first described by Sutton et al (1965), who demonstrated that infrequently-presented taskrelevant stimuli ("oddballs") produce a sequence of time-locked electrical components, the …”
Section: Orienting; Magnetic Resonance Imaging; Brain; Psychology; Comentioning
confidence: 99%